Safe and secure cyber‐physical systems. Issue 9 (16th March 2021) - Biró, Miklós; Mashkoor, Atif; Sametinger, Johannes
Abstract: Cyber‐Physical Systems (CPSs) differ from traditional Information Technology (IT) systems in such a way that they interact with the physical environment, i.e., they can monitor and manipulate real objects and processes. For this special issue, the authors of the best papers of IWCFS 2019 were invited to submit extended versions of their workshop papers. Additionally, we received eight submissions from around the globe as a result of an open call. After thorough and stringent reviews, we selected six articles that provide relevant contributions to the field of safety and security for CPSs.